Composition, strength and workability of alkali-activated metakaolin based mortars - Pacheco-Torgal, F. (2011)
This study has investigated the joint effect of several factors on the workability and mechanical strength of alkali-activated metakaolin based mortars. The factors analysed through a laboratory experiment of 432 specimens, pertaining to 48 different mortar mixes were, sodium hydroxide concentration (10 M,12 M, 14 M, 16 M), the superplasticizer content (1%, 2%, 3%) and the percentage substitution of metakaolin by calcium hydroxide in the mixture (5%, 10%). The results show that the workability decreases with the concentration of sodium hydroxide and increases with the amount of calcium hydroxide and superplasticizer. The results also show that the use of 3% of superplasticizer, combined with a calcium hydroxide content of 10%, allows improving the mortar flow from less than 50% to over 90%, while maintaining a high compressive and flexural strength.